Fluorescence Switches: Ferrocene‐Grafted Photochromic Triads Based on a Sterically Hindered Ethene Bridge: Redox‐Switchable Fluorescence and Gated Photochromism (Advanced Optical Materials 9/2016). Issue 9 (19th September 2016) - Cai, Yunsong; Gao, Ya; Luo, Qianfu; Li, Mengqi; Zhang, Junji; Tian, He; Zhu, Wei‐Hong
Abstract : On page 1410, a new gated photochromism and fluorescence switches are successfully achieved in a ferrocene‐modified diarylethene system with a sterically hindered ethene bridge. The photoinactive parallel conformer and photoactive antiparallel conformer are individually investigated by W.‐H. Zhu and co‐workers. The different conformers show redox‐gated photochromism and reversible redox reactions can also switch the fluorescence of the naphthalimide chromophore "ON" and "OFF".